Analisis Kepribadian Anak Ekstrovert Menurut Teori Carl Gustav Jung - Fadilah, Risydah; Juro, Az Zahra; Daifah, Cut; Rahmahwati, Dina (Lembaga Yasin AlSys, 2023)
Personality is a complete set of attitudes, behaviors, thoughts, feelings and values that influence individuals to do things according to their environment. In addition, personality is often interpreted as a prominent trait in a person, for example, a person who has a friendly nature will be a person with a